Upaya Pemberian Makna pada Prasasti Berbentuk Stambha dari Jawa Tengah (Abad IX–X Masehi) - Alnoza, Muhamad; Munandar, Agus Aris (UI Scholars Hub, 2021)
The Stone stele is made in a particular form based on a particular concept. The concept behind the making of the inscription is called meaning. Archaeologists need to interpret this in uncovering the meaning behind the inscription form by studying semiotics in the overall form and contents of the inscription. This paper studies the meaning of the stambha inscriptions from the 9th-10th century AD. The study is aimed at reconstructing the concept behind the making of the stambha inscriptions in ancient Java. The method used in this study consists of data collection, data analysis, and interpretation. Based on this series of studies, it can be seen that the stambha inscription has a hierarchical sacred meaning.